Quantifying the domestic building fabric ‘performance gap’ - Johnston, David; Miles-Shenton, Dominic; Farmer, David (Building services engineering research & technology, 2015)
In the UK, there is mounting evidence that the measured in situ performance of the building fabric in new build dwellings can be greater than that predicted, resulting in a significant building fabric ‘performance gap’. This paper presents the coheating test results from 25 new build dwellings built to Part L1A 2006 or better. Whilst the total number of dwellings reported here is small, the results suggest that a substantial ‘performance gap’ can exist between the predicted and measured performance of the building fabric, with the measured whole building U value being just over 1.6 times greater than that predicted. This is likely to have significant implications in terms of the energy use and CO2 emissions attributable to these dwellings in use. Practical application: This paper describes an aggregate approach (coheating test) that has been applied to a small sample of dwellings to quantify the size of the ‘performance gap’. The results suggest that this ‘gap’ can be large (>100%) and can vary depending upon form and construction type. The results also illustrate the importance of developing a larger, more representative whole dwelling heat loss data set. This could be used by industry to apply a suitable performance factor (note 1) to the nominal performance of new build that accounts for the ‘performance gap’. This factor could be specific to form and main construction type.